The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1017/jfm.2020.926
|View full text |Cite
|
Sign up to set email alerts
|

Curved surface effect on high-speed droplet impingement

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…higher than ) as studied by Kondo & Ando (2016) and Wu et al. (2018 b , 2021). Assuming homogeneous nucleation, Ando et al.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…higher than ) as studied by Kondo & Ando (2016) and Wu et al. (2018 b , 2021). Assuming homogeneous nucleation, Ando et al.…”
Section: Resultsmentioning
confidence: 68%
“…2016) or, as we already mentioned, a drop (Obreschkow et al. 2006; Gonzalez-Avila & Ohl 2016; Kondo & Ando 2016; Kyriazis, Koukouvinis & Gavaises 2018; Wu, Xiang & Wang 2018 b ; Wu, Liu & Wang 2021; Biasiori-Poulanges & Schmidmayer 2023). Laser cavitation in some of these configurations was lately applied in studies involving x-ray holography or x-ray diffraction to investigate the propagation of shock waves in liquids (Stan et al.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Field, Dear & Ogren (1989) and Field et al (2012) observed that, when a high-speed droplet impacts a rigid wall, convergence of reflected expansion waves could cause cavitation bubbles. The possibility of cavitation of a high-speed droplet impacting the wall was verified by Kondo & Ando (2016), Wu et al (2018) and Wu, Liu & Wang (2021b) via the numerical method. Xiang & Wang (2017) and Biasiori-Poulanges & El-Rabii (2021) expounded that the occurrence of cavitation inside the shocked water column is dependent on the incident shock wave intensity and the value of the cavitation threshold pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Multiphase flows with phase transitions and heat transfer are ubiquitous in natural and industrial processes, such as atmospheric phenomena, material and food processing, petrochemical engineering and bio-medicine, as well as life sciences (Brennen 2005; Bernaschi, Melchionna & Succi 2019; Zang et al. 2019; Wu, Liu & Wang 2021 b ). Therefore, establishing accurate, reliable and efficient models and computational strategies for predicting their flow behaviour will deepen our understanding of the fundamental and underlying physical mechanisms behind multiphase flows.…”
Section: Introductionmentioning
confidence: 99%